2018
DOI: 10.2478/amb-2018-0016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Citric Acid on the Vitality of Stem Cells from Apical Papilla

Abstract: The endodontic treatment of immature permanent teeth with necrotic pulp is a serious clinical challenge. The chemical agents, used in regenerative procedures, should be selected not only based on their bactericidal/bacteriostatic properties, but also on their ability to ensure the survival of the patient’s stem cells. The aim of this study was to evaluate the effect of citric acid on the vitality of SCAP in a model of an immature tooth root. Models of immature roots were created from 12 freshly extracted teeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In regenerative endodontics, Hristov et al suggested that 10% citric acid can be used in combination with 1.5% NaOCl, since there is no statistically significant difference between the effect of 10% citric acid and 17% EDTA on the vitality of SCAPs [35]. Moreover, Chae et al found that 10% citric acid is efficient for releasing TGF-β1 in vitro with more biocompatibility than EDTA [36].…”
Section: Citric Acidmentioning
confidence: 99%
“…In regenerative endodontics, Hristov et al suggested that 10% citric acid can be used in combination with 1.5% NaOCl, since there is no statistically significant difference between the effect of 10% citric acid and 17% EDTA on the vitality of SCAPs [35]. Moreover, Chae et al found that 10% citric acid is efficient for releasing TGF-β1 in vitro with more biocompatibility than EDTA [36].…”
Section: Citric Acidmentioning
confidence: 99%
“…Furthermore, it was possible to observe that 100% efficacy of disinfection was attained only after final irrigation with 17% EDTA [32]. Although EDTA has limited antimicrobial action, it has the capacity to remove the inorganic layer from the root canal walls by means of its chelating effect [44][45][46]. Therefore, it interferes in the adhesion, mass, viscosity and formation of biofilm on the intracanal dentinal surface [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Although EDTA has limited antimicrobial action, it has the capacity to remove the inorganic layer from the root canal walls by means of its chelating effect [44][45][46]. Therefore, it interferes in the adhesion, mass, viscosity and formation of biofilm on the intracanal dentinal surface [44][45][46]. Moreover, it is valid to emphasise that the use of EDTA exposes part of the organic portion of the dentinal matrix and its morphogenic proteins (growth factors) [47].…”
Section: Discussionmentioning
confidence: 99%
“…After the first screening (Step 1), 55 articles were selected and submitted to a full-text review (Step 2). Then, 19 studies were excluded, in which 13 (Arslan et al, 2014;Bosaid et al, 2020;Buldur et al, 2019;Ivica et al, 2020;Kandemir Demirci et al, 2020;Nagata et al, 2014;Nerness et al, 2016;Saghiri et al, 2016;Shawli et al, 2020;Ustun et al, 2018;Widbiller et al, 2018;Yassen et al, 2014Yassen et al, , 2015 were outside of the proposed theme, and 6 had no control group (Ferreira et al, 2020;Galler et al, 2011;Graham et al, 2006;Hristov et al, 2018;Tomson et al, 2007;Trevino et al, 2011; Figure 1). A total of 36 studies were included in the qualitative analysis and are presented in Tables 1, 2 and 3. The assessed Cohen's kappa coefficient for interinvestigator agreement during the studies' selection was 0.843 for PubMed, 0.970 for Scopus, 1.000 for the Cochrane Library and OpenGrey, 0.925 for the Web of Science and 0.876 for the Embase.…”
Section: Study Selectionmentioning
confidence: 99%